PENGARUH KONFLIK KERJA, STRES KERJA, KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Sensus pada karyawan Lotte Mart Tasikmalaya) - Irly Artiara Irawan; Evilia Sri Yuniar (LP2M Universitas Perjuangan Tasikmalaya, 2022)
This research to determine and analyst, the conflict of works, work stress, satisfaction and the performance of the employees on lotte mart tasikmalaya, the direct effect nor indirect of the conflict of works, work stress, satisfaction and the performance of the employees on lotte mart tasikmalaya. The research method that used in this study is census method. The study population is employees of lotte mart with amount 157 peoples. Technique of sample data on this research using total sampling technique which is all employees become sample data with amount 157 peoples. The data analyst technique using path analysis. The result of this research showed that the conflict of works, work stress, and work satisfaction significantly influenced partially and simultaneously to the performance of the employees on lotte mart tasikmalaya.